STUDI LABORATORIUM : ANALISIS PENGARUH JUMLAH REKAHAN TERHADAP PEROLEHAN MINYAK PADA KASUS HEAVY OIL DI RESERVOIR KARBONAT REKAH ALAMI - Angga, Kevin
It is estimated that over 60% of world oil and 40% of world gas reserves are produced from carbonate reservoirs. In the Middle East, it was dominated by carbonate reservoirs, there are over 70% oil reserves and 90% gas reserves that are produced by these reservoirs. Most of the reservoirs have two characteristics : matrix and fractures.The matrix gives the main oil storage capacity and the fractures gives the main oil flow. All of these characteristics made the carbonate reservoirs hard to produce efficiently and the oil recovery was so low. Oil stored in the carbonate rock matrix can be produced by using EOR methods. One of the EOR method that can be used is Chemical EOR methods or surfactant flooding. Therefore in this experiment used the injection of a chemical solution (surfactant Semar) to determine the effect of chemical solution injection at the fracture that are in carbonate rocks. Laboratory study was conducted through several steps of work by making carbonate reservoir artificial cores, spontaneous imbibition testing method, and coreflooding testing (dynamic imbibition). The making of carbonate reservoir artificial cores for modeling performed using a mixed composition of 30% quartz sand grains, 30% limestone grains, 30% cement, and 10% lime powder. Spontaneous imbibition testing is done with independent variable of Semar S14A * M 3% solution and the dependent variables of 3 types of number of fractures. Dynamic imbibition tests performed by injecting the Semar surfactant into core that have different numbers of fractures by using a series of Hassler Core Holder tools and syringe injector pump as a medium. The injection experiments were carried out with the use of several scenarios that use water (water flooding) and surfactant (surfactant flooding) with open-close time difference. Through these experiments can be seen that the greater the number of fractures, the oil recovery obtained will be even greater. With using SeMAR surfactant solution, it produced a change in wetting phase of oil to become strong wetting phase of surfactant solutions so the oil in the reservoir can be lifted.